Revitalizing The Role of Non-Formal Education Through PKW Entrepreneurial Innovation at Pkbm Teuku Markam - Akbar, Muhammad Ilham; Puspitasari, Savira Widya (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
This study critically examines the implementation of the Entrepreneurship Skills Education Program (PKW) at the Teuku Markam Community Learning Center (PKBM) as a strategic mechanism to revitalize the role of non-formal education in community empowerment. Although non-formal education is often marginalized as a secondary pathway, this study argues that its relevance can be restored through an empowerment-oriented and context-driven learning model. Using a qualitative approach with a descriptive case study design, data were collected through semi-structured interviews, observations, and document analysis involving institution leaders, tutors, and purposively selected learners. Data analysis followed an iterative process of reduction, categorization, and interpretation, supported by triangulation to ensure credibility. Findings indicate that the PKW program goes beyond conventional skills training by embedding learning within a structured empowerment framework consisting of awareness, capacity building, and empowerment stages. Beyond technical sewing competencies, the program fosters entrepreneurial skills, self-efficacy, and productive engagement among learners, particularly marginalized women. This demonstrates that non-formal education can serve as a transformative space that connects learning to livelihood outcomes. This study contributes to the discourse by repositioning entrepreneurship-based non-formal education as an instrument of socio-economic transformation, rather than simply a programmatic intervention. The study underscores that the revitalization of non-formal education depends on its ability to generate real and context-relevant impact.